IDENTIFICATION OF FAULT CONTINUITY AND HOT WATER RESERVOIR USE SCHLUMBERGER CONFIGURATION RESISTIVITY METHOD IN CANGAR - Dhony Widyasandy; Aulia K Nugraha; Husni Cahyadi Kurniawan; Ahmad Luthfin (Jurnal Neutrino: Jurnal Fisika dan Aplikasinya)
Research that uses the Schlumberger configuration resistivity method had been conducted in Cangar. The purpose of this study is to identify cracks/faults and potential hot springs use resistivity well analysis and correlate it with rock lithology in Cangar, East Java. Data acquisition is carried out using 3 tracks with 10 sounding points. The space between points is 50 meters. The rock resistivity values obtained were 9945 Ωm, 7360 Ωm, and 5573 Ωm which were thought to be breccia layers and functioned as hot springs. This estimation is strengthened by the existence of a layer of breccia-andesite because this layer is very good as a water reservoir. In addition, based on the lateral cross-section on lane 1, there was a decrease in boulder-sized breccia-andesite layers; this decrease was the production of faults.